In defense of primordialism: The Lithuanian case - Clark, Terry (Politologija, 1998)
With respect to the commitment of Lithuanians to an independent Lithuania state, in this article Terry Clark discusses the role of two theories - primordialism and contextualism. He introduces the method of analysis which best resolves his task - not so much to discuss applicability, the advantages of some particular theory, but instead - "to derive mutually exclusive propositions which are amenable to testing." The paper attempts to do so in the case of Lithuania using data as provided by a popular survey: "New Baltics Barometer II," conducted in 1995 by the University of Strathclyde's Centre for the Study of Public Policy.In the introduction, the author states that "most theorists of nationalism reject the primordialist view that ethnic identity is historically determined and firmly rooted in the consciousness of people groups." "Instead," he says, "they argue that ethnic identity is largely contextual." Having provided the brief characteristics of two views, plus the direction of the study, the author claims that "despite the consensus in favor of contextualism (that is, accommodative structural and institutional mechanisms and elements, which suppress chances of historical and identity cleavages," - remark of the summary-writer), scholars in Lithuania generally subscribe to the primordialist view." Herein, Terry Clark reminds the reader of a well-known American author, Alfred Erich Senn, whose book "The Baltic Revolution" is widely discussed in Lithuania, both among scholars and within society. The author claims: "Senn argues that Lithuania's struggle for the restoration of its independence largely resulted not from a rational calculus that the economic or political interests of the Lithuanian people would best be served outside of the Soviet Union, but rather from the re-emergence of the collective consciousness of the Lithuanian nation." Therefore, the implication is that to whatever extent the contextualist view prevails in the world, in Lithuania, the pendulum shifts towards the primordialist position: "when perestroika opened up possibilities for its expression, a 'primordial explosion' occurred."In the first section, titled "Rational Calculus or Nationalist Explosion?" the author notifies: "while both primordialists and contextualists identify the cause of ethnic discord and separatism as the presence of an 'us-them' dichotomy, they identify different reasons for the existence of the dichotomy. The proponents," - he says, - "differ radically on their explanation of the causes of the events which led to the restoration of Lithuanian independence." Provided the "us-them" foundation, the author, in respect to Lithuania, introduces the two theories. The primordialists, - Terry Clark postulates, - argue that the "us-them" dichotomy is historically conditioned based on the separate development of different people groups. It is reinforced by differences in language, culture, and historical experience. In this sense, the Lithuanian people perceive themselves "to be a nation, separate and distinct from the Russians." Viewing the case of the Soviet Union, they argue that this aforementioned aspect of ethnic distinctiveness was the primary predicament for the Lithuanians to condition their choice for ethnic separatism and an independent state. Furthermore, the author gives a mention of the role this position has, or may have, on the Lithuanians (for instance, negative predilection towards the Soviet past and Russians). (The theory excludes the proposition of contextualists that economic and political arrangements and theoretical arguments are of primary significance.)In contrast, contextualists view an "us-them" dichotomy as "emerging from a sense of deprivation, institutional impediments to the achievement of its interests, largely economic and political." From this perspective, the Lithuanian revolution is interpreted as "a choice based on a rational calculus of a higher payoff both economically and politically for an independent Lithuania rather than as a constituent part of a reconstructed Soviet Union." The contextualist view essentially argues that short-term cost-benefit calculations are more important to the evaluation of present-day Lithuania and Soviet Lithuania than are long-term historical and culturally conditioned responses.In due course, the propositions the author manages to derive from his review of primordialism and contextualism are mutually exclusive. He continues: "primordialism postulates that ethnic identity provides the greatest explanation for commitment to the post-independence of the post-Lithuanian state. The contextualists," - Terry Clark asserts, - "reject this notion, postulating instead that those individuals who evaluate the current economic and political system to be more efficacious will be more strongly committed to the post-independence Lithuania. Therefore, ethnic Lithuanians who most strongly identify themselves as such are more likely to express strong commitment to the newly independent state and to negatively evaluate the former Soviet Union."Data from the "New Baltics Barometer II" permit the author to test the propositions he introduces (several of them were mentioned above). In the section "Primordialist propositions," with complete reference to the data, he argues for several primordialist propositions. T. Clark claims: "the primordialist propositions argue that there is a strong correlation between ethnic identity and commitment to the Lithuanian state." Having provided us with the questions posed in the surveys, the author proceeds: "thus in determining the orientation of ethnic Lithuanians toward the independent Lithuania state, the most salient factor is positive self-identity as Lithuanians." Furthermore, he notifies that "Lithuanian self-identity, which focuses on exceptionalism from Russians, is more salient in explaining attitudes toward the former Soviet Union." In conclusion, he states: "the data support the primordialist propositions that ethnic self-identity is related positively with commitment to the independent Lithuanian state and negatively with support for the Soviet political system."In the following section, "The contextualist propositions," the author proceeds to claim the validity of the primordialist position: "the primordialist position is even more supported by the general failure of the contextualist propositions to gain a substantial degree of support from the data." The test of hypothesis shows the following: the negative evaluations of economic and political efficacy in comparison to a relatively high degree of commitment to the Lithuanian state and a very low degree of support for the former Soviet state indicates little support for contextualist contention that current cost-benefit calculations inform political loyalties of ethnic groups more so than ethnic identity. Therefore, in quite a literary manner, the author befouls the validity of the contextualist position in the case of Lithuania: "We are left to conclude that economic and political efficacy have no effect on identity with the Lithuanian state." However, the author precautions...
Keywords: -